2018
DOI: 10.1080/17476348.2018.1533405
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in chronic obstructive pulmonary disease: disease burden, determinants and possible future interventions

Abstract: Introduction: Cognitive impairment (CI) is an important but an under-recognized extra-pulmonary feature of chronic obstructive pulmonary disease (COPD). It is related to the burden of disability, worse health outcomes, and impaired self-management. Areas covered: CI includes deterioration of a wide range of cognitive functions, such as memory and various executive functions. Risk of hospitalization might be higher in patients with COPD compared to those without, with CI negatively impacting the wellbeing of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 140 publications
(176 reference statements)
0
28
1
2
Order By: Relevance
“…As indicated above, COPD is a disease characterized by chronic hypoxia [4,[6][7][8][9], which will lead to brain hypoxia, including the PFC. Thus, we speculate that patients with COPD might also be with spatial working memory deficits because of this chronic hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…As indicated above, COPD is a disease characterized by chronic hypoxia [4,[6][7][8][9], which will lead to brain hypoxia, including the PFC. Thus, we speculate that patients with COPD might also be with spatial working memory deficits because of this chronic hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Cognition is a series of advanced activities in the cerebral cortex, including perception, storage, retrieval, and use of information; such activities enables individual behaviors to adapt to new situations and functions in the environment. 10 Cognitive function includes many independent areas, such as memory, attention, executive ability, feeling, perception, thinking, learning and judgment. 11 When one or more of the above mentioned functions are impaired and affect the individual's activities of daily life, the patient has cognitive impairment.…”
Section: Copd and Cognitive Impairmentmentioning
confidence: 99%
“…41 Furthermore, to improve the inflammation, patients with COPD often use bronchodilators such as long-acting β-adrenoceptor agonist and long-acting muscarinic antagonist, which can also inhibit the central nervous system and cause damage to the attention function of COPD patients. 10…”
Section: Systemic Inflammationmentioning
confidence: 99%
“…Not surprisingly, people affected by chronic respiratory diseases show an increased risk of developing deficits in several cognitive functions (e.g. attention, mental flexibility, reasoning, memory and information processing speed) and developing mild cognitive impairment [41][42][43]. For example, a recent Dutch study demonstrated that of 183 people with COPD referred for pulmonary rehabilitation, 42% suffered from cognitive impairment as measured in a detailed neuropsychological test battery, and this prevalence was unrelated to the severity of COPD [44].…”
Section: Management Of Cognitive Dysfunctionmentioning
confidence: 99%